Experimental and numerical analysis of effect of fuel line length on combustion instability for H2/CH4 gas turbine combustor. (3rd November 2021) - Joo, Seongpil; Kwak, Sanghyeok; Yoon, Youngbin; Hong, Sumin; Kim, Daesik
Abstract: This study primarily aims to investigate the effects of fuel line length on the combustion instability characteristics of a partially premixed system. The key characteristics of combustion instabilities are analyzed in a H2 /CH4 fueled laboratory scaled model gas turbine combustor with a different fuel line length via dynamic pressure measurement, continuous wavelet transform, proper orthogonal decomposition, Rayleigh criterion analysis, and a numerical approach using a three-dimensional Helmholtz solver. It is discovered that the instability characteristics change with the fuel line length. In particular, when the resonance in the fuel line appears at frequencies similar to those of the various resonance modes in the combustion chamber, the corresponding resonance modes amplify each other, causing intense instability as those frequencies. Therefore, the acoustics of the fuel line or the geometry of the pre-chamber can be an important design parameter that affects the main characteristics of combustion instability in partially premixed combustion. Graphical abstract: Image 1 Highlights: The effects of changes in the fuel line length on combustion instability have been investigated. The instability characteristics change with the fuel line length. The fuel line geometry is an important design parameter affecting combustion instabilities.